Suitable Site Selection for Offshore Wind Farms in Turkey’s Seas: Gis-Mcdm Based Approach - Genç, Mustafa Serdar; Karipoğlu, Fatih; Karipoğlu, Fatih; Koca, Kemal; Azgın, Şükrü Taner (Springer, 2021)
Offshore wind energy resources are not fully exploited renewable energy resources until now and could play a crucial role in mitigating the impacts of climate change by the generation of renewable electricity. Planning processes such as technical, social, environmental, various agents, and political concerns are necessary for the development of offshore wind energy projects. The objective of this study was to assess the comprehensive feasibility of a desired offshore wind power plant applying Geographical Information Systems (GIS) and Multi-Criteria Decision-Making (MCDM) guidance for the coastal area of Turkey. Furthermore, EMODnet (the European Marine Observation and Data Network) was employed for data acquisition to unlock fragmented and hidden marine data resources and to facilitate investment in sustainable coastal and offshore activities. For the determination of potential site with Multi-Criteria Decision Maker Method, 3 main criteria Technical (C1), Environmental (C2), and Social (C3), and 13 sub-criteria were determined. Based on these criteria, the suitability map was created by using all criteria map layers with their buffer zones. The final map indicated that %1.38 (3294.8 km(2)) of Turkey Seas was suitable for offshore wind farms. The most suitable region was determined in the Marmara Sea with 1194 km(2). The Aegean Sea, the Black Sea, and the Mediterranean Sea were following the Marmara Sea in terms of the huge suitable regions respectively. It was apparent that the growth of offshore wind farms in Turkey would increase if the supporting mechanism and the necessary legislation were ensured.
Keywords: Renewable energy; Feasible site selection; Offshore wind farm; Geographic Information System (GIS); EMODnet